2019
DOI: 10.3390/nu12010082
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene Prevents Early Diabetic Retinopathy Alterations in a Rabbit Experimental Model

Abstract: Oxidative stress generated by diabetes plays a key role in the development of diabetic retinopathy (DR), a common diabetic complication. DR remains asymptomatic until it reaches advanced stages, which complicate its treatment. Although it is known that good metabolic control is essential for preventing DR, knowledge of the disease is incomplete and an effective treatment with no side effects is lacking. Pterostilbene (Pter), a natural stilbene with good antioxidant activity, has proved to beneficially affect d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…It is well-known that chronic hyperglycemia is a potent inductor of reactive oxygen species. In a recent study, using the current experimental model, we showed that hyperglycemia induces very early lipid oxidation in retina tissue of diabetic animals [ 7 ]. In addition, our group showed the ability of Pter to lower lipid peroxidation evaluated by 4-hydroxy-2-nonenal levels in diabetic treated animals [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is well-known that chronic hyperglycemia is a potent inductor of reactive oxygen species. In a recent study, using the current experimental model, we showed that hyperglycemia induces very early lipid oxidation in retina tissue of diabetic animals [ 7 ]. In addition, our group showed the ability of Pter to lower lipid peroxidation evaluated by 4-hydroxy-2-nonenal levels in diabetic treated animals [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols are the most abundant antioxidants in the human diet [ 31 ] and their beneficial effects have prompted interest in their use for treating retinal pathologies. For example, a protective effect has been observed against DR and other retinopathies with curcumin [ 32 , 33 ], resveratrol [ 34 , 35 , 36 ], quercetin [ 37 , 38 ], epigallocatechin gallate [ 39 , 40 ], and Pter [ 7 ], among others. The all have one thing in common, their antioxidant capacity against oxidative stress after hypoxia [ 41 , 42 ] and their significant ability to stop the pathological angiogenesis [ 43 ] by reducing levels of the vascular endothelial growth factor (VEGF) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations